Sport and Exercise Physiology Testing Guidelines: Volume I - Sport Testing. The British Association of Sport and Exercise Sciences Guide (Routledge, 2022)
Since its first published edition more than 30 years ago, the BASES (British Association of Sport and Exercise Sciences) Physiological Testing Guidelines have represented the leading knowledge base of current testing methodology for sport and exercise scientists. Sport and exercise physiologists conduct physiological assessments that have proven validity and reliability, both in laboratory and sport-specific contexts. A wide variety of test protocols have been developed, adapted and refined to support athletes of all abilities reach their full potential. This book is a comprehensive guide to these protocols and to the key issues relating to physiological testing.